2014
DOI: 10.5861/ijrsll.2014.955
|View full text |Cite
|
Sign up to set email alerts
|

Group dynamic assessment of EFL listening comprehension: Conversational implicatures in focus

Abstract: While the teachability of second language (L2) pragmatics has been the subject of considerable recent research interest (e.g. Bardovi-Harlig, 2011;Murray, 2011), testing the ability to infer implicatures in L2 has received limited attention (Roever, 2006). This study, therefore, tested the applicability of Group dynamic assessment (G-DA), rooted in Vygotskian socio-cultural theory (SCT), in assessing intermediate learners' pragmatic knowledge of conversational implicatures in the context of listening while sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…By doing so, the mediator was able to create a group ZPD through which she attempted to push individual learners' forward in their ZPD. These findings are in line with the results of previous DA studies on listening comprehension for example Ableeva (2010), Hidri (2014) andHashemi Shahraki et al (2015). Moreover, they accord with the results of DA studies done in a group format for example Lantolf and Poehner (2011), Davin (2013), and Gibbons (2003.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…By doing so, the mediator was able to create a group ZPD through which she attempted to push individual learners' forward in their ZPD. These findings are in line with the results of previous DA studies on listening comprehension for example Ableeva (2010), Hidri (2014) andHashemi Shahraki et al (2015). Moreover, they accord with the results of DA studies done in a group format for example Lantolf and Poehner (2011), Davin (2013), and Gibbons (2003.…”
Section: Discussionsupporting
confidence: 92%
“…Another study done in G-DA is Hashemi Shahraki, Ketabi and Barati (2015). In their study, they focused on the effects of group DA on learners' pragmatic knowledge of conversational implicatures in the context of listening.…”
Section: International Journal Of Research Studies In Education 19mentioning
confidence: 99%
“…In addition, Emadi and Arabmofrad ( 2015 ) showcased a comprehensive account of interactive listening and found that DA instructions boosted the test-takers to initiate developmental changes. Hashemi Shahraki et al ( 2015 ) carried out a study to estimate test-takers’ listening conversational implicatures of pragmatic knowledge and conveyed that the mediational support improved their pragmatic grasp of conversational implicatures. For Wang ( 2015 ), DA of listening enhances the amalgamation of assessment and instruction.…”
Section: Defining Listeningmentioning
confidence: 99%